TOPIC: THEORETICAL BASIS OF RESEARCHING THE WATER FACTOR IN THE REGIONAL SECURITY SYSTEM - Rikhsiboyev Baburjon Bakirjonovich (PT. Antis International Publisher, 2026)
Objective: This article examines the international-legal and institutional basics of water political to processes of transferring water as a possible tool for evaluation and his/her interstate relationships impact processes. Method: Water was theoretical views on water, geopolitical importance of water, international relationships in the system caught place analysis will be done. Results: The analysis demonstrates that cross-border water resources management significantly influences interstate relations, with legal and institutional frameworks shaping the transfer and allocation of water. Geopolitical considerations and the strategic importance of water create both opportunities and challenges for cooperation, highlighting the need for integrated management tools and evaluation mechanisms to mitigate conflicts and support sustainable water sharing. Novelty: This article evaluates cross-border water resources management from an international-legal and institutional perspective, focusing on its impact on interstate relationships and the political processes of water transfer.